An SLA-based resource scheduling method in hybrid cloud environment - UXiaofeng XU; Jinsong XU (Dianxin kexue)
Hybrid cloud provides a flexible approach to the application of local resources to the public cloud. A resource scheduling scheme with the minimum cost of external cloud resource constrained by SLA was presented. The key SLA measure of the outer part of the cloud was considered as the user’s satisfaction and the lowest cost. Then，the SLA component was quantized to dynamically adjust the internal cloud resource to be unable to service and need to dispatch resources. Experimental results show that the scheme can achieve the maximum satisfaction of cost and real-time performance.